(untitled) (Web of Teachers: Inderscience Research, 2025)
The article reveals the content of the concept of individual educational trajectories, analyzes the advantages of introducing individual educational trajectories into the system of higher professional education, substantiates the effectiveness and necessity of introducing individual educational trajectories into the educational process of the university.